Advances in Polymer Sciences and Technology Select Papers from APA 2017 - Gupta, Bhuvanesh; Ghosh, Anup K.; Suzuki, Atsushi; Rattan, Sunita; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents select papers presented at the annual meeting of the Asian Polymer Association. The chapters in this volume document and report on a wide range of significant recent results for various applications, as well as scientific developments in the areas of polymer science and engineering. The chapters include original research from all areas of polymer science and technology with a focus on the manufacture, processing, analysis and application of long chain polymer molecules. This book will be of interest to researchers in academia and industry alike. .
Synthesis of Lysine Mimicking Membrane Active Antimicrobial Polymers -- Structural and Morphological Analysis of Newly Synthesized Cuo@Alginate Nanocomposite with Enriched Electrical Properties -- Novel Polymeric Adsorbent for the Remediation of Cu (II) Ions from Water -- Artificial Neural Network Modeling to Predict Bacterial Attachment on Composite Biopolymeric Scaffold -- Triboelectric based Kinetic Energy Harvesting Using Polydimethylsiloxane (PDMS) -- Thermal Conductivity Enhancement of Epoxy Composite Based on Hybrid BN and Graphite Particulate Conductive Fillers and Effect of Hybrid Sample Thickness (T) and Filler Fraction on Thermal Resistance (R) and Thermal Conductivity (K) -- Antibacterial Activity of Antimicrobial Peptide (AMP) Grafted Polystyrene Surface -- Stabilization Studies of Epoxidized Soybean Oil Plasticized PVC Films in Presence Of beta-diketone Additives -- Homopolymer, Copolymers and Terpolymer Synthesis via Esterification-cum-Addition of N-Substituted Phthalimidewith Acrylates: Studies on Influences of Macromolecule Compositions on Thermal and Microbial Performances.-Multifunctional Compatibilizer for Polypropylene Blends With PMMA And EVA -- Polymer Nanocomposites: Modification Through Swift Heavy Ions -- Development of Hybrid Composites and Joining Technology For Lightweight Structures -- Starch-Chitosan blend Cross-Linked With Calcium Chloride -- Titania-Gelatin Based Nano-Hybrids: A Versatile Material For Removal of Organic Dyes (Congo Red; Malachite Green; Crystal Violet & Methylene Blue) From Aqueous Solution -- Formulation And Characterization of Poly (D,L-Lactide-co-Glycolide) Nanoparticles loaded with Achyranthes Aspera for Increasing Bioavailability -- Development of CNT-Polymer Film Based Electrode for the Detection of Glucose -- Anticancer Drug Loaded Folate Conjugated Multiwalled Carbon Nanotubes -- Designing And Nanofunctionalization of Infection Resistant Polyester Suture -- Efficient Extraction of Antioxidants and Lubricants from Commercial Polypropylene Pellets and their Quantification Using HPLC -- Mandelic Acid Incorporated Antimicrobial Soy Protein Film Fabricated by Solution Casting.
Keywords: Materials -- Analysis; Biomaterials; Polymers; Materials; Characterization and Analytical Technique; Biomaterials; Polymers; Materials Engineering